PRESENCE OF SCANDINAVIAN DESIGN ELEMENTS IN CHAIR MANUFACTURING IN MACEDONIA - Namicev, Petar; Shopova, Emilija (Journal of process management and new technologies, 2018)
Scandinavian design as a style, within the filed of furniture history and interior, emerges and develops in the aftermath of World War II in Central Europe, to be retained later in the Nordic countries: Sweden, Denmark and Norway. The Scandinavian modern style is mainly characterized by wood furniture with bright shades, pronounced lines, forms and shape. As one of the most popular leading domestic styles of today, the emphasis is placed on the design of furniture and interior, specifically the design of unique, simple and recognizable chairs. The concept and analysis of the research material refers to the presence of the Scandinavian design within the production of chairs in Macedonia, i.e. its influence, the chronology of development, characteristics of similar elements of design and production technology. The application of the basic elements to domestic production begins to gradually increase in the mid-1990s and achieve a high degree of representation of the characteristics of this style and at the same time the highest current market demand. Based on the carried out analyzes, Scandinavian style is present in the overall production of chairs in Macedonia, including inspiration and design, ergonomics, production stages and materials.